Impact of nanoparticles on human health and disease - Roy, Bedanta; Murugesan, Karthikeyan; Mathanmohun, Maghimaa; Sathian, Brijesh (Nepal Journal of Epidemiology, 2023)
Nanoparticles (NPs) are small particles with a surface area ranging from 1 to 100 nm in diameter that are rampantly used in different fields, e.g., medicine, engineering, and others. Because of their unique properties, such as their tiny size, magnetic properties, quantum size effects, and macroscopic quantum tunnelling effects, they are crucial for a wide range of potential applications. NPs play a significant role in the treatment of vascular disorders, the production of vaccines, and the development of drug carriers for diverse therapies due to their bioavailability, targeting ability, and efficacy. However, significant risks to the environment and health are also associated with it. NPs cause necrotic plasma membrane rupture or apoptosis, which leads to cell death. NPs interfere with cell signalling, endosomal membranes, and organelles like the nucleus or mitochondria, affecting their function. NPs cause autophagic cell death, which causes a stress response and sterile inflammation. The primary routes for the entry of NPs into the human body are inhalation, ingestion, and skin contact. NPs accumulate in the respiratory system based on their size, shape, and surface properties. NPs can cause lung inflammation and fibrosis, disrupt the endocrine system by attaching to hormone receptors, and produce reactive oxygen species (ROS) associated with DNA damage, oligospermia, and male infertility. Carcinogenic properties of NPs cause mutations, apoptosis, and inflammatory responses. Collaborative research between ecologists and epidemiologists may enlighten ways to reduce the harmful effects of NPs.